Kualitas dan kuantitas sample sangat menentukan kualitas hasil suatu penelitian, karena dari karakter sample-lah karakter suatu polpulasi akan digeneralisasi sebagai hasil dari suatu pene-litian. Ukuran sampel yang tepat sangatlah sulit ditentukan, hal - sariayu agustina muslicha; Ken Sudarti (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2011)
For service firms, the essence of marketing is the development of long-term, value-laden relationship with customers. Relationship commitment and relationship outcomes have been essential for successful long-term relationship. This study is purposed to identify the impact of communication effectiveness, trust, service quality and relationship commitment on relationship outcomes in professional services. Two-step approach to structural equation modeling was used to test the proposed model. 125 customers as clients of the financial planners services   was used as respondents in this study. The result of this study indicates that the communication effectiveness directly do not influence both relationship commitment and relationship outcomes. The impact of communication effectiveness on relationship commitment and relationship outcomes is mediated by service qualities (technical and functional qualities). Key words: Professional services, Communication effectiveness, Trust, Relationship marketing, Service quality, Services marketing